TRANSFER KNOWLEDGE FEASIBILITY STUDY DALAM PENERAPAN TEKNOLOGI DOCKING KAPAL PADA GALANGAN KAPAL TRADISIONAL - Arie Saputra; Fitriadi Fitriadi; Iing Pamungkas; Said Fadhlain (Jurnal Pengabdian Agro and Marine Industry, 2026)
This community service activity aims to improve the understanding of traditional shipyard stakeholders regarding the importance of feasibility studies in implementing ship docking technology. The program was conducted at CV Wahana Karya, a traditional shipyard in Pasi Pinang Village, Meureubo District, West Aceh Regency, involving the owner, director, and operational workers. A participatory knowledge transfer approach was applied through three stages: preparation, implementation, and evaluation. The materials covered feasibility study concepts, their role in decision-making, and the potential benefits of docking technology. Data were collected through observation, discussion, and participant feedback, and analyzed descriptively. The results show an increased understanding among participants regarding the role of feasibility studies in supporting efficient and informed decision-making. However, implementation readiness remains limited due to financial constraints, workforce preparedness, and resistance to change. This activity demonstrates that knowledge transfer is essential in bridging research and practice and serves as an initial step toward improving operational efficiency in traditional shipyards.